Improving Reading Comprehension of the Second Grade Students by Using Graphic Organizer - Ahmad Syukron Sidik (IKIP PGRI Bojonegoro, 2019)
Abstract The preliminary research of this research showed that the students had problems with reading comprehension known from their score. The students got 55 as their reading comprehension score where as the score of the student’s report card was 68. Therefore, this present study employed Classroom Action Research (CAR) which involves four stages of research. They were (1) Planning, (2) Implementing, (3) Observing, and (4) Reflecting. The instruments used to collect data in this research are field note, observation checklist, and reading comprehension test. This research was done in one cycle which consists of three meeting and it set score 63 in average as the criterion of success based on the researcher and the English teacher discussion. This criterion of success considered the students’ reading comprehension ability and the classroom circumstance. The result of this study above draws us into the conclusion that the graphic organizer Method improves the student’s reading comprehension. This proved by the increasing of their score and behavior during the implementation of the method. Thus, graphic organizer method is an effective method in improving student’s reading comprehension. Keywords: Reading comprehension, graphic organizer method, classroom action research AbstrakStudi pendahuluan dari penelitian ini menunjukkan bahwa siswa memiliki masalah dengan kemampuan membaca yang diketahui dari skor mereka. Para siswa mendapat 55 sebagai skor pemahaman bacaan mereka sedangkan skor kartu laporan siswa adalah 68. Oleh karena itu, penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) yang melibatkan empat tahap penelitian. Mereka adalah (1) Perencanaan, (2) Implementing, (3) Observing, dan (4) Reflecting. Instrumen yang digunakan untuk mengumpulkan data dalam penelitian ini adalah catatan lapangan, daftar observasi, dan tes membaca pemahaman. Penelitian ini dilakukan dalam satu siklus yang terdiri dari tiga pertemuan dan menetapkan skor rata-rata 63 sebagai kriteria keberhasilan berdasarkan pada peneliti dan diskusi guru bahasa Inggris. Kriteria keberhasilan ini mempertimbangkan kemampuan pemahaman membaca siswa dan keadaan kelas. Hasil penelitian ini di atas menarik kita ke kesimpulan bahwa Metode grafik organizer meningkatkan pemahaman membaca siswa. Ini dibuktikan dengan meningkatnya skor dan perilaku mereka selama implementasi metode. Dengan demikian, metode grafik organizer adalah metode yang efektif dalam meningkatkan pemahaman membaca siswa. Kata kunci: Pemahaman membaca, metode grafik organizer, penelitian tindakan kelas